2006
DOI: 10.1211/jpp.58.10.0012
|View full text |Cite
|
Sign up to set email alerts
|

Relaxant effect of Crocus sativus (saffron) on guinea-pig tracheal chains and its possible mechanisms

Abstract: As indicated in ancient Iranian medical books, Crocus sativus has therapeutic effects on respiratory diseases. The relaxant effect of this plant has been observed also on smooth muscles in previous studies. Therefore, in this study the relaxant effects of aqueous-ethanolic extracts of C. sativus and one of its main constituents, safranal, were examined on guinea-pig tracheal chains. The relaxant effects of four cumulative concentrations of aqueous-ethanolic extract (0.15, 0.3, 0.45, and 0.60 g %) and safranal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
92
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 17 publications
10
92
2
Order By: Relevance
“…Such studies included but are not limited to the menthol compounds found in Mentha piperita (peppermint) which also possessed additional pulmonary enhancing functions [18], thymol and carvacrol, both phenolic terpenoid compounds, isolated from Origanum syriacum [19], [20], the latter of which was identified as a potential bronchodilator using animal models [21]. The phyto-compound; cineole, found within the essential oils of Eucalyptus globulus and Rosmarinus officinalis [22] has been implicated and documented as an anti-inflammatory agent which ameliorates chronic bronchitis, a condition triggered by either bacteria (Mycoplasma pneumonia, Bordetella pertussis, Moraxella catarrharis, Haemophilus influenza) or induced by rodents [22].…”
Section: Introductionmentioning
confidence: 99%
“…Such studies included but are not limited to the menthol compounds found in Mentha piperita (peppermint) which also possessed additional pulmonary enhancing functions [18], thymol and carvacrol, both phenolic terpenoid compounds, isolated from Origanum syriacum [19], [20], the latter of which was identified as a potential bronchodilator using animal models [21]. The phyto-compound; cineole, found within the essential oils of Eucalyptus globulus and Rosmarinus officinalis [22] has been implicated and documented as an anti-inflammatory agent which ameliorates chronic bronchitis, a condition triggered by either bacteria (Mycoplasma pneumonia, Bordetella pertussis, Moraxella catarrharis, Haemophilus influenza) or induced by rodents [22].…”
Section: Introductionmentioning
confidence: 99%
“…The constituents of F. asafoetida include thymol (10%) (29), which did not show any relaxant effect on tracheal smooth muscle (1), ambelliprenin (less than 1%), which showed significantly lower relaxant effect compared to the plant extract (27) and carvacrol, which showed a potent relaxant effect on tracheal smooth muscle (30). The inhibitory effect of carvacrol on muscarinic receptors of tracheal smooth muscle was also observed previously (31).…”
Section: Discussionmentioning
confidence: 51%
“…The authors concluded that Crocus sativus induced potent relaxant effect on tracheal chains of guinea-pigs that was comparable to or even higher than that of theophylline at the concentrations used. The results also indicated that safranal was, at least in part, responsible for the relaxant effect of Crocus sativus [76].…”
Section: The Prophylactic Effect Of Saffron (Crocus Sativus)mentioning
confidence: 76%